Malignant Pheochromocytoma in a 16-Year-Old Patient with Neurofibromatosis Type 1. (March 2014) - Giovannoni, Isabella; Callea, Francesco; Boldrini, Renata; Inserra, Alessandro; Cozza, Raffaele; Francalanci, Paola
Patients with neurofibromatosis type I (NF1) feature a high risk of developing benign and malignant tumors, mainly those with a neuroectodermal origin, the risk being about 4 times higher than in the general population. Pheochromocytoma (PHEO) is a sporadic tumor (1∶100 000) arising from the adrenal medulla. Pheochromocytoma is a rare condition when occurring in conjunction with NF1 and occurs in about 1% of patients, rarely in those of pediatric age. In this study we present a 16-year-old patient with NF1 and malignant PHEO. Loss of heterozygosity analysis in PHEOs shows a reduction to homozygosity, observed for both 17p and 17q markers. This case confirms the importance of surveillance for malignant neoplasias in NF1 patients during childhood and adolescence. On the other hand, since 30% of PHEOs had germline mutations and, more rarely, somatic mutations, patients with PHEO should be investigated for associated genetic syndromes.